(untitled) (Stato, Chiese e pluralismo confessionale, 2019)
SOMMARIO: 1. Premessa - 2. L’incapacità consensuale nel matrimonio - 3. Evoluzione della Giurisprudenza ecclesiastica - 4. Le nuove dipendenze - 5. Le radici della dipendenza patologica - 6. Sex addiction - 6a - Dipendenza da pornografia - 6b. Dipendenza da cyber pornografia - 7. Dipendenza dal lavoro (Work addiction) - 8. Il collezionismo patogeno - 9. Dipendenza dalla chirurgia estetica - 10. Dipendenza dallo shopping - 11. Dipendenza da selfie - 12. Dipendenza dal gioco d’azzardo - 12a. Dipendenza da Trading on line - 12b. Dipendenza dai videogiochi - 13. Dipendenza dallo sport o exercise addiction - 14. Internet addiction e psicotecnologie - 14a. Dipendenza da email - 15. Dipendenza dalla televisione - 16. L’incidenza delle nuove dipendenze sulla capacità di intendere e di volere - 16a. Gli effetti delle nuove dipendenze sulla capacità consensuale matrimoniale - 17. Considerazioni conclusive. New dependencies in relation to the ability to issue a valid matrimonial consent ABSTRACT: This article identifies and outlines the new addictions or psychiatric disorders that, whilst not deriving from the abuse of substances, still manages to make a person incapable of self-determination and make free and mature decisions. In recent years, the psychological distress in which many people find themselves living is taking on specific characteristics and is affected by social and cultural elements that make the process of developing emotional-affective skills, the possibility of having a certain identity and the achievement of stable balances very hard. To the already known pathologies are therefore added new ones often associated with borderline-narcissistic personality disorders; drug-free addictions are to be counted among the psychiatric disorders in which social, cultural, economic and psychological elements emerge. Those elements make these new problems interesting and relevant in the present-day but also difficult to insert into certain diagnostic frames.